Food selection of wintering common cranes (Grus grus) in holm oak (Quercus ilex) dehesas in south-west Spain in a rainy season - Avilés, Jesús M; Sánchez, Juan M; Parejo, Deseada (Journal of Zoology, 2006)
In the holm oak Quercus ilex dehesas of the Iberian Peninsula, several food types occur that can be selected by birds through the winter. In this framework, diet composition and diet selection of common cranes Grus grus was studied during a rainy wintering season. The winter diet of the common crane is mostly herbivorous in the holm oak dehesas of south-west Spain with < 10% of items being of animal origin. Leaves and stems of sown cereal, bulbs, acorns and cereal grain are the most common vegetable food types. The diversity of the overall winter diet was similar among juveniles and among adults with and without juveniles in attendance. However, there were differences in diet composition between juvenile birds and their parents. Furthermore, the diet composition of adult cranes with juveniles in attendance was different from that of adult cranes without juveniles in attendance. Foraging abilities of juvenile cranes did not vary signi®cantly through the winter, suggesting a low effect of experience on diet differences between age classes. Our results point toward the existence of diet differences among the three considered crane categories related with differential habitat selection by family groups. The monthly pattern of choice of each food type differed from those expected according to the monthly pattern of food availability in the study area. Cereal grain was the most preferred food type when it was available. When cereal seed germinated, cranes shifted to acorns and bulbs which were then more pro®table
Keywords: age differences; Common Crane; food selection; Grus grus; holm oak dehesas; Quercus ilex

Time budget and habitat use of the Common Crane wintering in dehesas of southwestern Spain - Avilés, Jesús M (Canadian Journal of Zoology, 2003)
In many bird species juvenile inexperience drastically reduces their survival, and parents must provide for them. I tested whether time budget and habitat use in adult wintering Common Cranes (Grus grus) in dehesas (pastoral woodland) of western Spain were affected by the presence of juveniles. Juvenile cranes devote less time to vigilance and spend more time feeding than adults in dehesas. Likewise, juveniles are involved in fewer aggressive encounters than adult cranes. Contrary to expectation, adults accompanied by juveniles devoted the same amount of time to vigilance and feeding and had the same intake rate than adults without juveniles in attendance. However, adult cranes with offspring in attendance were involved in more aggressive encounters than adults without juveniles in attendance when both adult groups were involved in large flocks. In contrast, when adults accompanied by juveniles were in small flocks they were involved in fewer aggressive encounters than adults without juveniles. I also detected a differential use of dehesas by adult cranes that was linked to juvenile presence and explained by the vulnerability of juvenile cranes in intraspecific social relationships. Adults with juveniles in attendance preferred dehesas with livestock where flock sizes were smaller than those in dehesas without livestock, and therefore where they might reduce the number of aggressive encounters with other cranes.
doi: 10.1139/z03-105
Keywords: Cranes; Dehesa; feeding (voyant); intake rate; livestock; parental investment; social structure